Marriage and inequality in Chinese society - Watson, Rubie S. (Rubie Sharon), 1945-; Ebrey, Patricia Buckley, 1947- (Studies on China ;, 1991)
Until now our understanding of marriage in China has been based primarily on observations made during the twentieth century. The research of ten eminent scholars presented here provides a new vision of marriage in Chinese history, exploring the complex interplay between marriage and the social, political, economic, and gender inequalities that have so characterized Chinese society.